Consequences of anthropogenous influence on the air of the Stavropol region and men's health - R. S. Sigida (Юг России: экология, развитие)
Influence of air pollution in Stavropol district on health of the population is analyzed. Dominating sources and kinds of substances polluting the atmosphere are revealed. The contribution of various industries to air pollution of Stavropol district is certained. There is made the analysis of the consequences of carbon oxide, nitrogen oxide, hydrocarbons and other substances influence on occurrence and development of various pathologies.